Analisis Hukum Pelanggaran Hak Cipta melalui Situs Streaming Ilegal - Kusumah, Akhmad Hadi; Suhartini, Endeh; Nurwati, Nurwati (Syntax Corporation, 2025)
In this research, the main problem is first, what are the steps for legal protection of cinematography copyright on illegal streaming sites. Second, what are the legal efforts for cinematography copyright holders on illegal streaming sites. This thesis research uses a normative legal approach, namely a legal research method carried out by examining library materials or secondary data. The results of this study are First, the steps for legal protection of cinematography copyright on illegal streaming sites where the Copyright Law provides automatic protection to creators once their creations are physically born, creations that are not registered with the Directorate General of Intellectual Property Rights also receive the same legal protection. However, the process of proving unregistered creations will experience difficulties at the level of proof in court, because in practice there are many cases where creators have difficulty proving their ownership of the creation. therefore, proof of copyright ownership is something important and formal that becomes initial evidence of a creation, but in reality, in practice in the field, that copyright violations still occur, such as the increasingly rampant Illegal Streaming Sites, unstoppable illegal circulation, and copyright violations of moral rights and other economic rights. Second, Legal efforts for Cinematography Copyright holders in illegal streaming sites carried out and/or provided by the State through the Copyright Law in criminal and civil manner. The fairly high criminal sanctions are a reflection of the commitment of the Republic of Indonesia government to provide maximum protection against copyright infringement.